Vascular response and healing profile of everolimus-eluting bioresorbable vascular scaffolds for percutaneous treatment of chronic total coronary occlusions: A one-year optical coherence tomography analysis from the GHOST-CTO registry. (15th February 2018) - La Manna, Alessio; Miccichè, Eligio; D'Agosta, Guido; Tensol Rodrigues Pereira, Gabriel; Attizzani, Guilherme Ferragut; Capranzano, Piera; Capodanno, Davide; Tamburino, Corrado
Abstract: Background: Bioresorbable vascular scaffolds (BVS) have been heralded with potential benefits that are especially desired in long lesions, including chronic total occlusions (CTOs). Procedural feasibility and mid-term outcomes of BVS in CTOs have been reported. However, there is still a paucity of data regarding the vascular and healing response to BVS in CTOs evaluated by optical coherence tomography (OCT). Methods: This study included prospectively 21 patients who had a CTO lesion treated with a BVS. Angiography and OCT scan were recorded at either post-implantation and 1-year follow-up. Quantitative coronary angiography and OCT analyses were performed by an independent core laboratory. Results: The angiographic analysis showed a significant increase in the percentage of in-segment diameter stenosis at 1 year (11.89 ± 9.5% vs. 21.84 ± 11.7%; p  = 0.002). The OCT analysis showed a trend ( p  = 0.07) towards increased mean scaffold area and significant reductions in mean lumen diameter (3.1 ± 0.36 mm vs. 2.85 ± 0.47 mm; p  = 0.0046), mean lumen area (7.8 ± 1.73 mm 2 vs. 6.76 ± 2 mm 2 ; p  = 0.0082) and minimal lumen area (5.26 ± 1.86 mm 2 vs. 3.56 ± 1.52 mm 2 ; p  < 0.0001). Malapposition area and volume decreased from 0.26 ± 0.17 mm 2 to 0.08 ± 0.1 mm 2 ( p  = 0.0003) and from 14.17 ± 12.92 mm 3 to 3.99 ± 4.46 mm 3 ( p  = 0.0014), respectively. The rate of uncovered or malapposed struts, measured at the frame level, was 5.29 ± 6.48% at 1 year. Conclusions: In a small series of CTO patients treated with BVS implantation, OCT outcomes at 1 year displayed an overall favorable vascular response and healing profile.